Empowerment through Teaching and Research: County-level Breakthrough in the Normalized Development of Research and Study Practice for Left-behind Children and the Construction of the "Zhaozhou Model" ——An Empirical Study and Path Reflection Based on Hongqi Primary School in Zhaozhou County - Mingming Wang; Mingli Wang (Education Research on Study Tours and Practice, 2026)
Against the backdrop of the strategy of building a powerful country in education and rural revitalization, left-behind children are confronted with severe challenges such as lack of parental affection, narrowed horizons and unbalanced quality development. As a "classroom without walls", research and study practice serves as a key carrier to make up for the growth shortcomings of left-behind children and promote educational equity. Nevertheless, the current research and study practice for left-behind children at the county level is mired in fragmented activities, homogenized content and weak teachers, making its normalized development difficult. Taking Hongqi Primary School of Zhaozhou County, Daqing City, Heilongjiang Province as a case, this paper adopts the action research method and in-depth interview method to systematically sort out the practical process of the school constructing a three-level progressive research and study system of "classroom-campus-off-campus" with "teaching and research empowerment" as the core leverage. The research shows that creating localized music research and study courses, developing characteristic content featuring "low cost, high emotion and strong experience", and establishing an integrated mechanism of teaching, research and training for teachers can effectively break resource constraints and realize the paradigm transformation of research and study practice from occasional activities to normalized operation. The "Zhaozhou Experience" refined in this study provides a replicable empirical model for similar agricultural counties to promote the care work of left-behind children from material assistance to spiritual prosperity.